1996
DOI: 10.1016/s0896-6273(00)80112-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Cellular Aspects of Nicotine Abuse

Abstract: conducting cations, and are in desensitized or inactive states while unresponsive to agonist. The likelihood of *Division of Neuroscience Baylor College of Medicine being in a particular state depends on many factors, including the nAChR subtype, the agonist concentra-Houston, Texas 77030-3498 † Molecular Neurobiology Laboratory tion, and the rate of agonist application. A rapid pulse of agonist causes synchronized activation of nAChRs, The Salk Institute San Diego, California 92186-5800 but long-term exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
367
0
9

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 552 publications
(382 citation statements)
references
References 23 publications
6
367
0
9
Order By: Relevance
“…Occupancy of these deep desensitized states by nicotine could serve as the trigger for up-regulation in receptor number (Dani and Heinemann, 1996;Fenster et al, 1999b), shown to occur in vivo for ␣4␤2 nAChRs during chronic nicotine exposure (Marks et al, 1983;Schwartz and Kellar, 1985;Flores et al, 1992;Balfour, 1994); this again could potentially involve biochemical steps, because chronic nicotine promotes enhanced ␣4 subunit phosphorylation (Hsu et al, 1997). While controversy exists over whether prolonged agonist exposure results in up-or down-regulation of receptor function (Buisson and Bertrand, 2002), recovery from this "state," whether it requires purely time (slow transition rates) or de novo receptor synthesis (Boyd, 1987;Hsu et al, 1996), likely influences synaptic transmission for prolonged periods.…”
Section: Regulation Of Desensitizationmentioning
confidence: 99%
“…Occupancy of these deep desensitized states by nicotine could serve as the trigger for up-regulation in receptor number (Dani and Heinemann, 1996;Fenster et al, 1999b), shown to occur in vivo for ␣4␤2 nAChRs during chronic nicotine exposure (Marks et al, 1983;Schwartz and Kellar, 1985;Flores et al, 1992;Balfour, 1994); this again could potentially involve biochemical steps, because chronic nicotine promotes enhanced ␣4 subunit phosphorylation (Hsu et al, 1997). While controversy exists over whether prolonged agonist exposure results in up-or down-regulation of receptor function (Buisson and Bertrand, 2002), recovery from this "state," whether it requires purely time (slow transition rates) or de novo receptor synthesis (Boyd, 1987;Hsu et al, 1996), likely influences synaptic transmission for prolonged periods.…”
Section: Regulation Of Desensitizationmentioning
confidence: 99%
“…A common feature of many addictive drugs, including nicotine, is that they increase dopamine (DA) levels in the nucleus accumbens (NAcc) at the same concentrations that are achieved in serum during selfadministration (Stolerman and Jarvis, 1995;Dani and Heinemann, 1996;Picciotto et al, 1998;Dani and De Biasi, 2001). The principal dopaminergic projections to the NAcc arise from neurons in the VTA (Fig.…”
Section: Nicotinic Receptors and Addictionmentioning
confidence: 99%
“…In the PNS, nAChRs mediate fast excitatory synaptic transmission. In the CNS, their functions also include modulating neurotransmitter release from presynaptic terminals, reinforcing nicotine addiction, and increasing attention, arousal and memory formation (Dani and Heinemann, 1996;Jones et al, 1999;Perry et al, 1999). Abnormalities in nAChR number and function have been implicated in neurologic disorders such as Alzheimer's disease, Parkinson's disease, familial frontal lobe epilepsy, and auditory-gating schizophrenia (Lena and Changeux, 1997;Court et al, 2000).…”
Section: Introductionmentioning
confidence: 99%